Optimizing the Defense Logistics Transportation System in Indonesia: A Case Study on Military Logistics - Sarjito, Aris (CV Insan Kreasi Media, 2024)
This research investigates the optimization of the defense logistics transportation system in Indonesia, focusing on the Indonesian Armed Forces. The study aims to identify key components and stakeholders in the defense logistics transportation system, explore the main challenges and obstacles faced in optimizing the system, and propose strategies to improve its efficiency and effectiveness. Utilizing qualitative research methods, secondary data from government reports, academic publications, and industry sources are analyzed. Key findings reveal the intricate network of components and stakeholders involved in the defense logistics transportation system, including government agencies, military branches, private contractors, and international partners. Major challenges identified include inadequate infrastructure, limited resources, bureaucratic inefficiencies, and security concerns. These challenges impede the timely and cost-effective delivery of essential supplies to military operations. The research concludes by proposing strategies to address these challenges and enhance the efficiency and effectiveness of the defense logistics transportation system. These strategies encompass infrastructure development, capacity building, technology integration, collaboration among stakeholders, and policy reforms.